Wellness-туризм як сервісна інновація індустрії гостинності - Сильчук, Тетяна Анатоліївна; Кирпіченкова, Оксана Миколаївна; Друзь, Тетяна Павлівна (My University, 2023)
У статті сформулювало дефініцію «wellness», як концепції здорового способу життя, гармонійного поєднання фізичного та ментального здоров’я, правильного харчування, розумних фізичних навантажень, відмови від шкідливих звичок тощо. Виокремлено основні ознаки wellness-туризму як сучасної сервісної інновації. Розглянуто взаємопов’язані стани людини, що дозволяють комплексно сформулювати wellness-концепцію. Визначено особливості, функціональне спрямування й тенденції розвитку wellness-туризму в індустрії гостинності. Встановлено, що сервісні wellness-інновації здійснюють профілактичний вплив на стан здоров'я людини. Обґрунтовано, що wellness-туризм як інноваційний напрям рекреаційної індустрії активно інтегрується в ринкове середовище відповідно до нових запитів та потреб суспільства. The article defines the essence of "wellness" as a concept of a healthy lifestyle, a harmonious combination of physical and mental health, proper nutrition, reasonable physical exertion, and giving up bad habits. The main features of wellness tourism as a service innovation are highlighted. Interrelated states of a person, which allow to form the concept of wellness, are considered. The features and trends of the development of wellness tourism in the hospitality industry are determined. It has been established that service wellness innovations have a preventive effect on human health. It is substantiated that wellness tourism as an innovative direction is actively integrated into the market environment in accordance with new requests and needs of society. Wellness tourism has a special organization and, accordingly, stages of implementation, because it is mainly carried out by healthy people who do not need medical supervision. The main motive and purpose of such tourism is to strengthen and preserve health. Most experts note that wellness tourism not only prevents diseases, but also promotes the development of mental qualities of the human personality. The main goal of wellness services is the prevention and prevention of diseases, as well as maintaining physical activity, achieving an anti-aging, anti-stress effect. This is the main difference from health services of medical tourism. Today, the transformation of recreational tourist complexes is due to the following reasons. A healthy lifestyle becomes a priority. The number of people who want to maintain good physical shape is increasing. For example, to restore your body with the help of anti-stress or antiaging programs. They cover not only classic recreation courses, but also various means for relaxation. The second reason is the reorientation of budget support for recreational tourist establishments. Due to the unstable economic and political situation, traditional financial support from the state is being reduced. This forces sanatorium-type establishments to improve their product in order to enter new segments of the consumer market and attract additional customers.
Keywords: кафедра готельно-ресторанної справи; wellness-туризм; wellness-концепція; wellness-інновація; wellness-стан; індустрія гостинності; здоровий спосіб життя; релаксація; wellness tourism; wellness concept; wellness innovation; wellness state; hospitality industry; healthy lifestyle; relaxation